Politeness Strategies and Gender Differences in Javanese Indirect Speech Acts - Putri Ramadhani; Busmin Gurning; Berlin Sibarani (Universitas Negeri Medan, 2014)
The objectives of this study were to identify types of politeness strategies, to examine the differences of politeness patterns used by different gender and to see how the politeness strategies imply in the culture of “indirectness” a culture of Javanese who avoid being direct to utter something which were reflected in Javanese indirect speech acts in request. The approach used in this study are based on politeness theory of Brown & Levinson (1987); Bald-on record, Positive, Negative, and Off Record. This study employed descriptive qualitative design. The data were the transcription of recorded observation and interview using audiovisual recorder in Javanese social interaction in doing business transaction at “PasarRebo”, a traditional market in Deli Serdang, North Sumatera. The politeness strategies used were bald-on record strategy, positive politeness strategy and negative politeness strategy. Different strategies were performed by different gender; male dominantly used bald-on record strategy while female dominantly used positive politeness strategy. The realization of Javanese indirect speech acts used by female established an indirect correlation to politeness strategies and the culture of “indirectness” in Javanese. The realization of these politeness strategies by the speakers were aimed to minimize Face Threatening Acts to endeavor a harmony in social interaction. Keywords: Gender; Indirect speech act; Politeness strategiesement if they were taught by using TBL model.